2014
DOI: 10.1016/j.cub.2014.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Object Size in Retinotectal Microcircuits

Abstract: Ethologically relevant size classes are preferentially processed in different layers of the tectal neuropil. The tectum categorizes visual targets on the basis of retinally computed size information, suggesting a critical role in visually guided response selection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
141
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(153 citation statements)
references
References 47 publications
12
141
0
Order By: Relevance
“…In order to dissect the role of individual neural components of tectal circuitry in generating the population activity encoding critical angle, we analyzed activity patterns in two distinct neural cell types: retinal ganglion cells (RGCs) that send axons into the four input layers of the OT (SO, SFGS, SGC, SAC, (Nikolaou et al, 2012)), and superficial inhibitory interneurons (SINs), which have been shown to play a significant role in filtering out large (Del Bene et al, 2010) as well as small (Preuss et al, 2014) moving visual stimuli. In order to measure activity in RGC terminals, we generated a transgenic fish line (UAS:SyGCaMP6s) in which GCaMP6s (Chen et al, 2013) is linked to synaptophysin and expression in RGCs is driven by an Isl2b:Gal4 line (Figure 4A (Nikolaou et al, 2012)).…”
Section: Resultsmentioning
confidence: 99%
“…In order to dissect the role of individual neural components of tectal circuitry in generating the population activity encoding critical angle, we analyzed activity patterns in two distinct neural cell types: retinal ganglion cells (RGCs) that send axons into the four input layers of the OT (SO, SFGS, SGC, SAC, (Nikolaou et al, 2012)), and superficial inhibitory interneurons (SINs), which have been shown to play a significant role in filtering out large (Del Bene et al, 2010) as well as small (Preuss et al, 2014) moving visual stimuli. In order to measure activity in RGC terminals, we generated a transgenic fish line (UAS:SyGCaMP6s) in which GCaMP6s (Chen et al, 2013) is linked to synaptophysin and expression in RGCs is driven by an Isl2b:Gal4 line (Figure 4A (Nikolaou et al, 2012)).…”
Section: Resultsmentioning
confidence: 99%
“…When this nutrient need was met, nutrient intake dropped, and larvae were satiated. This behavior occurred on a 2-h timescale and likely modulated the visual-motor programs required for hunting behavior (4,26,33). Upon meal ingestion, food is digested within the gastrointestinal tract.…”
Section: Discussionmentioning
confidence: 99%
“…Although it has been shown that tectal cells have preferences for particular stimuli features (Bianco & Engert, 2015;Hunter et al, 2013;Preuss et al, 2014), the cells responding as part of an assembly can vary across trials. To determine whether the cells in our trials were responding consistently, the matching index (MI) was calculated for each assembly across the five trials in each animal (Romano et al, 2015).…”
Section: Assemblies Are Highly Variable Trial To Trial But Contain Rmentioning
confidence: 99%
“…While the different roles of two classes of core cells described above remain unknown, they may represent activation of different populations of inhibitory interneurons versus excitatory, efferent cells. Inhibitory neurons have been shown to be critical in the zebrafish tectum to the filtering of large visual information , Preuss et al, 2014 and are also likely to influence direction selectivity (Grama & Engert, 2012). Likely to be an important direction for future research will be determining the role of these cells in deciding which networks of cells become activated in response to particular stimuli.…”
Section: Assembly Coresmentioning
confidence: 99%
See 1 more Smart Citation